(untitled) (Research, Society and Development, 2021)
Basic sanitation is an essential component of contemporary urban life. Thus, the school needs to include activities on this topic in its educational practices. Given these premises, the objective of this article is to analyze the view of students from Middle School about basic sanitation aiming to obtain subsidies for the construction of appropriate educational practices. The activities carried out involved the application of questionnaires with open and closed questions and dialogical presentations. The qualitative information was examined with Content Analysis and the quantitative information with the Kruskal-Wallis Test. The results indicated the need to problematize the subject in different disciplines, including activities that point to the interrelationships between the four areas of basic sanitation aiming to enable students for public debates on this theme.